90.8k views
5 votes
Find x so that (-5)^x+1 x (-5)^5 = (-5)^7

User CharanRoot
by
4.4k points

2 Answers

2 votes

Answer:

x = 1

Explanation:

Using the rule of exponents


a^(m) ×
a^(n) =
a^((m+n)) , then


(-5)^(x+1) ×
(-5)^(5) =
(-5)^(7)


(-5)^((x+1+5)) =
(-5)^(7)


(-5)^(x+6) =
(-5)^(7)

Since bases on both sides are the same , both - 5 , then equate exponents

x + 6 = 7 ( subtract 6 from both sides )

x = 1

User Alexojegu
by
4.6k points
2 votes


\\ \sf\longmapsto (-5)^(x+1)* (-5)^5=(-5)^7


\boxed{\sf a^m* a^n=a^(mn)}


\\ \sf{:}\implies (-5)^(x+1+5)=(-5)^7


\\ \sf{:}\implies (-5)^(x+6)=(-5)^7


\\ \sf{:}\implies x+6=7


\\ \sf{:}\implies x=7-6


\\ \sf{:}\implies x=1

User Omar Abdelhafith
by
4.6k points